2017
DOI: 10.1371/journal.pone.0178774
|View full text |Cite|
|
Sign up to set email alerts
|

Does a presentation’s medium affect its message? PowerPoint, Prezi, and oral presentations

Abstract: Despite the prevalence of PowerPoint in professional and educational presentations, surprisingly little is known about how effective such presentations are. All else being equal, are PowerPoint presentations better than purely oral presentations or those that use alternative software tools? To address this question we recreated a real-world business scenario in which individuals presented to a corporate board. Participants (playing the role of the presenter) were randomly assigned to create PowerPoint, Prezi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 78 publications
2
26
0
1
Order By: Relevance
“…The model of teaching through lectures, centred on the teacher, still plays a central role and dictates the mainstream pedagogical strategy of higher education teaching (Pros & Tarrida, 2017;Garrett, 2016;Akbar, 2016;Moulton, Türkay & Kosslyn, 2017). In the context of application of this teaching model, there is currently some generalisation of the use of electronic slideshow presentations (ESP) in higher education classes, especially in the form of a PowerPoint slideshow or, more recently, in Prezi (Inoue-Smith, 2016;Naik, 2017;Chou, Chang, & Lu, 2015;Babbs & Ross, 2009;Tejada-Llacsa & Cahuana-Aparco, 2016;Worthington & Levasseur, 2015;Schoeman, 2013;Hill, Arford, Lubitow, & Smollin, 2012;Kosslyn, Kievit, Russell, & Shephard, 2012;Garrett, 2016), although there is no unanimity regarding the merits of this software (Inoue-Smith, 2016;Pros & Tarrida, 2017;Moulton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model of teaching through lectures, centred on the teacher, still plays a central role and dictates the mainstream pedagogical strategy of higher education teaching (Pros & Tarrida, 2017;Garrett, 2016;Akbar, 2016;Moulton, Türkay & Kosslyn, 2017). In the context of application of this teaching model, there is currently some generalisation of the use of electronic slideshow presentations (ESP) in higher education classes, especially in the form of a PowerPoint slideshow or, more recently, in Prezi (Inoue-Smith, 2016;Naik, 2017;Chou, Chang, & Lu, 2015;Babbs & Ross, 2009;Tejada-Llacsa & Cahuana-Aparco, 2016;Worthington & Levasseur, 2015;Schoeman, 2013;Hill, Arford, Lubitow, & Smollin, 2012;Kosslyn, Kievit, Russell, & Shephard, 2012;Garrett, 2016), although there is no unanimity regarding the merits of this software (Inoue-Smith, 2016;Pros & Tarrida, 2017;Moulton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of application of this teaching model, there is currently some generalisation of the use of electronic slideshow presentations (ESP) in higher education classes, especially in the form of a PowerPoint slideshow or, more recently, in Prezi (Inoue-Smith, 2016;Naik, 2017;Chou, Chang, & Lu, 2015;Babbs & Ross, 2009;Tejada-Llacsa & Cahuana-Aparco, 2016;Worthington & Levasseur, 2015;Schoeman, 2013;Hill, Arford, Lubitow, & Smollin, 2012;Kosslyn, Kievit, Russell, & Shephard, 2012;Garrett, 2016), although there is no unanimity regarding the merits of this software (Inoue-Smith, 2016;Pros & Tarrida, 2017;Moulton et al, 2017). This article addresses presentations in both PowerPoint and Prezi, given that there seem to be no clear and undeniable advantages in terms of learning using one or the other program (Chou et al, 2015;Moulton et al, 2017), although there is a clear dominance of PowerPoint use (Garrett, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…16 Corresponding research also explained that students were more interested in Prezi than Powerpoint. 11 The high students' interest in visual media could be useful to achieve the learning objectives. Students' interests may contribute to students' motivation to give more attention to the given learning material.…”
Section: Discussionmentioning
confidence: 99%
“…Certain research concluded that students found that Prezi is more interesting than any other presentation media. 11 Prezi could also stimulate students to be more productive in writing the report. 12 In this case, nursing education learns about humans as the learning object.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presentation and sharing students' learning results played an essential role for student's perception in classroom climate and therefore influence their learning. In fact, research has revealed that presentation methods will affect student's cognitive results (Moulton et al 2017), and clear digital presentation could enhance retention and promote learning effects. Future classroom optimization should consider using technology to facilitate student's presentation and sharing of learning contents.…”
Section: Discussionmentioning
confidence: 99%